2003
DOI: 10.1124/jpet.102.048520
|View full text |Cite
|
Sign up to set email alerts
|

Improved Brain Uptake and Pharmacological Activity of Dalargin Using a Peptide-Vector-Mediated Strategy

Abstract: The blood-brain barrier restricts the passage of substances into the brain. Neuropeptides, such as enkephalins, cannot be delivered into the brain when given systemically because of this barrier. Therefore, there is a need to develop efficient transport systems to deliver these drugs to the brain. Recently, we have demonstrated that conjugation of doxorubicin or penicillin to peptide vectors significantly enhances their brain uptake. In this study, we have conjugated the enkephalin analog dalargin with two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 26 publications
3
65
0
1
Order By: Relevance
“…at ASPET Journals on May 12, 2018 jpet.aspetjournals.org mine whether this is due to enhanced penetration of the BBB, as has been reported for other PTD-drug conjugates (Rousselle et al, 2003). The exact mechanism underlying this difference is a matter of active investigation, and our unpublished data suggest that COG133 interferes with certain intracellular signal transduction pathways (N. Ohkubo, C. A. Colton, F.-Q.…”
Section: Apoe Mimetics Ameliorate the Disability Of Eae 963supporting
confidence: 58%
“…at ASPET Journals on May 12, 2018 jpet.aspetjournals.org mine whether this is due to enhanced penetration of the BBB, as has been reported for other PTD-drug conjugates (Rousselle et al, 2003). The exact mechanism underlying this difference is a matter of active investigation, and our unpublished data suggest that COG133 interferes with certain intracellular signal transduction pathways (N. Ohkubo, C. A. Colton, F.-Q.…”
Section: Apoe Mimetics Ameliorate the Disability Of Eae 963supporting
confidence: 58%
“…Our results confirm our previous reports that vectorization of drugs with SynB vectors results in an enhancement of brain uptake and pharmacological activity (Rousselle et al, , 2002(Rousselle et al, , 2003Blanc et al, 2004). In the present study, our rationale was to attach M6G to the SynB3 peptide vector to enhance its brain uptake.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, we have shown that small peptide vectors can be used to enhance brain uptake of various drugs without opening the tight junctions (Rousselle et al, , 2002. The potential of this approach as an effective brain delivery system has been demonstrated for various drugs (Rousselle et al, , 2002(Rousselle et al, , 2003Blanc et al, 2004).…”
mentioning
confidence: 99%
“…Moreover, the K D values measured for the Syn-B transport reside in the micromolar range, and compare well with the values observed for molecules described as being taken up by adsorptive-mediated endocytosis. Similar characteristics of transport were demonstrated for the cell uptake of Syn-B vectors conjugated to a fluorophore (27) or various drugs (34,69,70).…”
Section: Selected Cppsmentioning
confidence: 58%
“…Indeed, many cargo models used to demonstrate the ability of CPPs to efficiently translocate small or large molecules into cellsfor example fluorescent probes or the GFP or beta-galactosidase tags-have no therapeutic value whatsoever. However, there are several examples where CPPs have been used successfully to deliver therapeutic molecules through the BBB and into the brain, but as it stands today, most examples are limited to low molecular weight drugs and small peptide drugs (34,69,70,76). The first benchmark study of the ability of CPPs to deliver proteins across the BBB is probably that of Schwarze and Coll.…”
Section: In Vitro Delivery To Cells and In Vivo Delivery To Brain Tissuementioning
confidence: 99%